"This choice does not just affect me." Attitudes of pregnant women toward COVID-19 vaccines: a mixed-methods study - Sarah Geoghegan; Laura C. Stephens; Kristen A. Feemster; Richard J. Drew; Maeve Eogan; Karina M. Butler (Taylor & Francis Group, 2021)
Public health experts agree that pregnant women who fall into priority groups may be offered a Coronavirus Disease 2019 (COVID-19) vaccine. However, little is known about attitudes of pregnant women toward COVID-19 vaccination. We surveyed 300 pregnant women during the roll out of the Pfizer-BioNTech vaccine in Ireland. Women rated likelihood of receipt of a vaccine during pregnancy, on a 1-10 scale (1 = very unlikely, 10 = very likely). One hundred and thirteen (38%) women responded with a score of ≥8, while a similar proportion (36%) selected a score of ≤2. Safety of their unborn infant was the primary driver of decision making among survey participants, but specific safety concerns differed according to likely acceptance of a vaccine. Communication about COVID-19 vaccines to pregnant women must explicitly address safety. Pregnant women and their health-care providers should be supported with accessible interpretations of data so that they can make the best choice for their individual risk profile.